Four new free-living marine nematode species (Sabatieria) from the Chukchi Sea - Yang, Peipei; Guo, Yuqing; Chen, Yuzhen; Lin, Rongcheng (Zootaxa, 2019)
Four new free-living marine nematode species of the genus Sabatieria are described from the Chukchi Sea. Sabatieria chukchensis sp. n. is characterized by a long body (2052–2326 μm), two pairs of short cervical setae present, amphideal fovea spiral with 2.75–3.25 turns, and seven papilliform pre-cloacal supplements. Sabatieria parvamphis sp. n. is characterized by small amphideal fovea (equal to 55–72% corresponding body diameter), amphideal fovea spiral with 3.25 turns, short cephalic setae (6–7 μm, equal to 31–38% of head diameter), curved gubernacular apophyses, thirteen to fifteen prominent tubular pre-cloacal supplements with distance between adjacent supplements increasing towards the anterior. Sabatieria major sp. n. is characterized by a long body (3879–4255 μm), amphideal fovea spiral with 2.5–3.25 turns, and seventeen to thirty-two small tubular pre-cloacal supplements. Sabatieria multisupplementia sp. n. is characterized by a long body (3967–4294 μm), amphideal fovea spiral with 2.75–3 turns, and forty-one to forty-seven tubular pre-cloacal supplements.